Consolation amidst the Suffering The Great War and its place in the history of Dutch neo-Calvinist theology - Striekwold, Robbert (Studium, 2014)
This article looks at how neo-Calvinist theologians, Abraham Kuyper and Herman Bavinck in par- ticular, dealt with theological problems posed by the First World War. These included, most notably, the question of how to reconcile Christianity with the idea of war, and how to give war meaning in a Christian worldview. Here I will argue that the first of these two questions did not present a problem, as neo-Calvinist orthodoxy had ready answers for it. The second, however, was much more difficult and indeed proved to be intractable. I will argue that some of the hardships the Dutch churches faced during and after the war were due to their failure to formulate a convincing answer for this problem, as their theology required them to defend the idea of war against the pacifists. This failure led to a general belief that the traditional theological answers the churches had to offer no longer sufficed.